Filtração de gases a altas pressões - Franco, Kleber Serrão (2012)
The filtration of gases is an important industrial operation with the primary aim of removing unwanted solid particles contained in a gas. The filtration of gases at high pressures is an operation widely used in natural gas industry with the aim of separating impurities called black powder, from rust inside pipelines along the transportation. These residues can cause wear on equipment such as, for example, rotor pump, obstruction of gauges and pressure decrease in product quality. Despite being an operation widely used, few studies exist in the area to study what the best type of filter. Therefore this study is very useful to improve the steps of transportation, measurement and purity of the final product. To simulate this process, we used the dry compressed air, injecting a phosphate rock as particulate matter. The filters were tested RAD cellulose and acrylic. The surface speed of filtration was kept constant at 0.05 m / s, throughout the filtering operation. The flow of compressed air used were 14 l / min to the total pressure 1 bar, 42 l / min at a total pressure of 3 bar and 86 l / min at a total pressure of 6 bar. Total load losses were 5, 10, 20 and 30 mbar. The results showed that, initially, the curves of head loss versus deposited mass showed the same growth trend. However, when forming a layer of cake from about 0.03 kg/m2, the filtrations higher pressures had lower pressure loss. This is because the larger pressure forming pies more porous and less resistant to air flow. At the end of the study it was also observed that the acrylic filter performed better compared to the cellulose RAD, due to its greater mass of accumulated dust and low pressure drop.